(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The aim of this essay is to investigate what the relationship of emotions and metaphors in different expressions in English language using different language units. In emotion metaphors reveals about the connections between something utterly concrete, such as motion, and something very abstract, such as emotion.